Food access and associated socioeconomic factors in the Durham-Chapel Hill Metropolitan Statistical Area (MSA), North Carolina - Zahra Al Hamdani; Matthew Jansen; Tia Marie Francis; Philip McDaniel; Lisa Jo Melnyk (PLoS ONE, 2025)
The adversity of diet-related diseases is increased because of food insecurity . North Carolina is higher than the national average (11.7%) in food insecurity at 13.9%. The availability of healthy foods in households depends on the spatial access within the food environment where people reside or work. This study characterized the food environment, food access and associated socioeconomic factors in the Durham-Chapel Hill metropolitan statistical area (MSA) at a census block group level. Using GIS and statistical techniques, the average weighted median (AWM) was devised as measure of access for food outlets; associations between the AWM and socioeconomic variables were then investigated using multivariate regressions. For everyone in the MSA, the analysis showed lowest accessibility for fruit and vegetable markets (AWM = 2), and the highest accessibility for restaurants (AWM = 136). Relative to the White population, percentage point increase in the African American population in a block group led to a statistically significant increase in access to all categories of food outlets, with the highest increase in access of fruits and vegetable markets at 4% (p < 0.001). For every person increase in household size a decrease there was a decrease in the AWM of fruit and vegetable markets and food banks by 40%. The approach used in this study can be used in across localities measure access at a higher geographic granularity (block group level) and the associated sociodemographic factors. The results highlight disparities in food access which may require public health interventions.